PENGARUH SUPLEMENTASI TEPUNG MAGGOT BLACK SOLDIER FLY (BSF) DALAM RANSUM TERHADAP TOTAL LEUKOSIT DAN DIFERENSIAL LEUKOSIT DARAH AYAM JOPER - Nabila, Amara; Suharyati, Sri; Fathul, Farida; Hartono, Madi (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2024)
This study is aimed to determine the effect of maggot flour on total leukocytes and differential leukocytes of joper chickens. This research was conducted in January–March 2022 at the Joper Daffa Chicken Farm, Labuhan Dalam, Tanjung Senang District, Bandar Lampung City. Examination of total leukocytes and differential leukocytes was carried out at the Pathology Laboratory, Lampung Veterinary Center, and Animal Reproduction Physiology Laboratory, Animal Husbandry Department, Faculty of Agriculture, Lampung University. The experimental design used was 4 treatments and 5 replications. The treatments were ration without supplementation of maggot flour (P0), ration with 5% maggot flour supplementation (P1), ration with 10% maggot flour supplementation (P2), and ration with 15% maggot flour supplementation (P3). The data obtained were arranged in the form of simple tabulations and displayed in the form of histograms for descriptive analysis. The results showed that the treatment with suplementation of maggot flour was able to maintain an average of total leukocytes and an average of differential leukocytes in the normal range. The value of total leukocytes obtained was 22.59–25.07 x 103/mm3; heterophils was 27–29%; eosinophils was 4–6.75%; basophils was 1.25–2%; lymphocytes was 53.5–57%; and monocytes was 9.6–11.4%.